Economic globalization and the role of the EU social policy as challenge (not only) for Central and Eastern Europe - Martin Potůček (Social Work & Society, 2019)
Is the European Union pro-social? Or does it merely pretend it in order to hide its real face, that of an institutional mediator of interests of powerful economic actors in the era of economic globalization? Questions like this are not purely academic in nature because answers to them can suggest a lot about the Union's future fate and a lot about the broader political processes of (dis)integration taking place on our continent. This contribution offers a general overview of the key political and economic determinants and outcomes of social policy developments in Central and Eastern Europe. The special attention is devoted to the conditions of the accession of new member states into the EU, coinciding with the victorious ideological discourse of neoliberal orthodoxy. It has set the tone of public debate and politics on a global level and has been much easier to promote in the post-communist world than in the established western democracies. Since 1989, a decisive segments of political representatives, the media and the general public there have not managed to free itself from the idea that the primary goal of societal efforts should be a booming economy, and that human lives, capabilities and skills are merely the tools necessary for achieving this overarching goal.